HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN BPJS DI INSTALASI RAWAT JALAN RSUD LABUANG BAJI MAKASSAR TAHUN 2019 - Andi Rizky Amaliah (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2021)
Patient satisfaction is a function of the patient's assessment of the health services provided by the hospital in the hope that before the patient receives health services from the hospital as a provider, the patient will feel satisfied if the quality of hospital services is higher or at least the same as what the patient expects. This study aims to determine the relationship between physical evidence, reliability, responsiveness, assurance and empathy with BPJS patient satisfaction. The results showed that the quality of service physical evidence (Tangibles) p (0.76)> 0.05 which means there is no relationship, reliability (reliability) p (0.01) <0.05 which means there is a relationship, responsiveness (responsiveness). ) p (0.03) <0.05, which means there is a relationship, assurance p (0.00) <0.05 which means there is a relationship, empathy (empathy) p (1.00)> 0.05 which means no relationship. The conclusion in this study is that there is no relationship between physical evidence service quality and empathy with patient satisfaction, and there is a significant relationship between service quality reliability, responsiveness, and assurance with BPJS patient satisfaction. It is suggested to the hospital to further improve service quality, reliability, responsiveness, and assurance in order to increase BPJS patient satisfaction.